Strategies for Designing Effective Lesson Plan in Micro Teaching Practices Perceived by Indonesian EFL Student Teachers - Sherly Alfiani; Ivan Achmad Nurcholis (English Learning Innovation (englie), 2023)
This article aims to analyze the strategies of 6th-semester students of one of the private universities in Bengkulu in designing a lesson plan for their Microteaching courses. This research was qualitative and used interviews to collect data, as well as using descriptive patterns to present data, not using numbers. Interviews were used in this study to find out what strategies were used by sixth-semester students of the English Department. The results of this study highlighted the preparation of the teaching process, the problems faced by pre-service teachers, and some strategies they use in preparing lesson plans. This article is expected to provide a better understanding of strategies for designing a lesson plan.